Practices of growth assessment in children: Is anthropometric measurement important? - Jose RL Batubara (Indonesian Pediatric Society, 2005)
Assessing and monitoring growth iscommon practice in pediatric care, andhealth professionals accept routine growthmonitoring in children as a standardcomponent of community child health servicesthroughout the world. In clinical level, by theseactivities one can detect and intervene while growthfaltering happens. The internationally recommendedway to assess malnutrition at population level is to takeanthropometric measurements. In developedcountries, growth monitoring is an intrinsic part of‘well child’ clinics. As growth is a proxy for childhealth, the child who grows well is generally healthyand illness in a child is usually associated with poorgrowth. Interpretation of child growth is based onanthropometric indicators established in a referencepopulation with cut-off points to differentiate under-and overnutrition, short stature or tall stature,proportionate or disproportionate growth. Practicesof growth monitoring consist of regularly measuringthe weight and height of children, then plotting theinformation on a growth chart to make abnormalgrowth visible. When growth is abnormal, the healthworker does something in concert with the family andas a result of these actions the child receivesappropriate social or medical support, his or hernutrition improves, or a serious condition is diagnosedearlier.